Archives and historians of sport - Martin Johnes (International Journal of the History of Sport, 2015)
Archives and the documents within them are at the heart of the practice of history and the occupational culture of historians. A majority of historical work has been characterized and defined by research in archives of varying kinds. Yet, the material within archives is both partial and political and using it is never straightforward. For historians of sport, the material available in archives can be especially limited but, with some careful reading between the lines, there is still much to learn from and interpret within traditional archives. This paper explores the different kinds of archives and archival material that historians of sport have used and the uses they have been and can be put to. Archives, however, are not static entities and the paper also discusses the impact and implication of digitization processes and programmes to popularize and legitimize traditional archives. Although sport has been seen as one of the ways of diversifying the content and audience of archives, the paper argues that the practical and interpretative challenges historians of sport face in archives are no different to those faced by other historians.